Distal embolization durante percutaneous coronary intervention: a case report - Betty Dwi Lestari, Budi Yuli Setianto (Universitas Gadjah Mada, 2011)
Distal embolization is an acute complication of percutaneous coronary intervention (PCI). Distal embolization ofplaque and thrombus material is considered as a major cause of insufficient reperfusion despite a fully patent infarctrelatedartery, apart from ischemic microvascular damage and reperfusion-induced regional inflammatory responses.In a recent study, angiographic evidence of distal embolization was associated with an 8-fold increase in 5-yearmortality.We reported on our experience with distal embolization durante PCI which lead the patient developed STElevationMyocardial Infarct (STEMI) inferior and posterior accompanied with severe chest pain and was treated inthe Intesive Coronary Care Unit (ICCU). Distal embolization is the case that we should be put into our awarenessbecause it can worse the after procedural outcome.Key words: distal embolization-percutaneous coronary intervention-insufficient reperfusion- myocardial ischemiaangiographic